Implementation of the Return to Work Program as a Guarantee for Protection of Workers' Rights at PT. SPINDO Surabaya - Bagijo, Himawan Estu; Hindiawati , Wahyu (Jurnal Hukum dan Keadilan, 2024)
Social security in Indonesia is contained in the constitution. The content of this social security is regulated in article 28 H paragraph (3) of the 1945 Constitution of the Republic of Indonesia which states "that every person has the right to social security which enables his/her full development as a dignified human being". The Social Security Administering Body or often abbreviated as BPJS plays a very important role in carrying out its duties. One of them is providing social security and improving the welfare of all Indonesian workers in accordance with the Vision and Mission of BPJS Employment. Return to work is one of the new programs from BPJS Employment. The legal basis underlying the Return to work program includes: Government Regulation Number 44 of 2015 concerning the Implementation of Work Accident and Death Insurance Programs, Minister of Manpower Regulation No. 10 of 2016 concerning Procedures for Providing Return to Work Programs as well as Promotional Activities and Preventive Activities for Work Accidents and Work-related Diseases. The aim of this research is to determine the implementation of Return to Work at PT. Steel Pipel Industry of Indonesia (SPINDO) and to determine the inhibiting and supporting factors for the Return to Work program at PT. SPINDO. This research uses empirical legal research methods. Meanwhile, the results of the research show that: 1) PT. SPINDO has implemented the Return to Work Program ; 2) factors inhibiting the return to work program at PT. SPINDO almost doesn't exist. Meanwhile, the supporting factors for this return to work program include: first , socialization has been carried out by BPJS Ketenagakerjaan Karimunjawa to PT. SPINDO. Second , the facilities are adequate at PT. SPINDO is able to support the implementation of the return to work program .